Current indications of imaging in abdominal wall hernias (2019)
Abdominal wall hernias in their different modalities form a group of commonly encountered surgical conditions. They vary in their presentation from asymptomatic to life threatening emergencies. Clinical history and physical examination are the primary methods for diagnosis, however in a significant percentage of patients, a normal physical examination can be found. Due to this, diagnostic imaging has been gaining attention in recent years, which in addition to identifying the cases of abdominal hernias with normal physical examination, provide additional relevant data. In this article we review available literature regarding the usefulness of diagnostic imaging such as herniography, ultrasound (US), computed tomography (CT) and magnetic resonance imaging (MRI) for the diagnosis of abdominal wall hernias. CT and ultrasound are the main modalities used for the diagnosis and characterization of the hernia defect. CT is recommended when there is uncertainty in the diagnosis after the physical examination or initial ultrasound, or as a first option if complications are suspected. Evaluation using imaging is important both as a diagnostic tool and for an adequate anatomical characterization in patients with suspected abdominal wall hernias. © 2019 Sociedad Hispanoamericana de Hernia. Publicado por Arán Ediciones, S.L. Todos los derechos reservados.